2020
DOI: 10.1177/1071100720939884
|View full text |Cite
|
Sign up to set email alerts
|

Tibiotalocalcaneal Fusion With Antibiotic Cement-Coated Nails for Refractory Deep Infection After Ankle ORIF

Abstract: Background: Deep infection after open reduction internal fixation (ORIF) of ankle fractures represents a challenge to the orthopaedic surgeon, particularly in patients in whom conventional surgical treatments have failed. The aim of this study was to assess the results of a modified technique of tibiotalocalcaneal fusion using a retrograde locked intramedullary nail covered in cement with antibiotics. Methods: Six patients treated using the authors’ technique were analyzed retrospectively. All patients had dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(33 reference statements)
0
2
0
1
Order By: Relevance
“…Авторы сообщают о возможности выполнения нескольких ревизий. Так, например, для санации очагов инфекции после осложнений остеосинтеза переломов лодыжек M. Herrera-Pérez с соавторами говорят о том, что количество ревизионных вмешательств у каждого пациента варьировало от 3 до 7 при среднем количестве 5 операций [15]. В нашем случае было выполнено три последовательных ревизии, и только последняя из них была завершена полным укрытием раны.…”
Section: описание клинического случаяunclassified
“…Авторы сообщают о возможности выполнения нескольких ревизий. Так, например, для санации очагов инфекции после осложнений остеосинтеза переломов лодыжек M. Herrera-Pérez с соавторами говорят о том, что количество ревизионных вмешательств у каждого пациента варьировало от 3 до 7 при среднем количестве 5 операций [15]. В нашем случае было выполнено три последовательных ревизии, и только последняя из них была завершена полным укрытием раны.…”
Section: описание клинического случаяunclassified
“…It was reported that the BAI rate was between 2.6 and 45% if tibial plateau fractures managed with Open Reduction and Internal Fixation (ORIF) in bone fracture fixation clinically [3,4]. A new type of treatment strategy that antibiotic-loaded bone cement was covered on intramedullary nail achieved significant effect for deep infection after ORIF of ankle fractures [5]. Bone cement can form a strong bond in situ with bone tissue to create a mechanically stable interface under the influence of tensile, compressive, and shear forces [6].…”
Section: Introductionmentioning
confidence: 99%
“…Revision arthrodesis or fixation in the presence of current or previous infection carries a high risk of recurrence and persistence of an infected nonunion, thus presenting significant challenge. 23 In revision surgery, technical issues arise from the osseous voids left behind because of the required resection of diseased bone and tissue back to healthy, bleeding margins. Successful arthrodesis and bone healing requires preservation of bone and structural support to bridge any achieve stable fixation and compression of opposing bone interfaces for union.…”
Section: Introductionmentioning
confidence: 99%